2004
DOI: 10.1097/01.olq.0000140018.24262.4a
|View full text |Cite
|
Sign up to set email alerts
|

Community-Based Survey of HIV Transmission Modes Among Intravenous Drug Users in Sichuan, China

Abstract: The results of this study suggested total times of sharing injection equipment in the past 3 months and syphilis infection were significantly associated with HIV infection. Further seroepidemiologic prospective cohort studies should be conducted to clarify the impact of syphilis and high-risk sexual behaviors on HIV transmission through unprotected sexual intercourse.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
41
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(42 citation statements)
references
References 9 publications
0
41
1
Order By: Relevance
“…Sharing of needles and paraphernalia in particular drives the epidemic in many countries outside Africa (Aceijas, Stimson, Hickman, & Rhodes, 2004;Fuller et al, 2003;Ruan et al, 2004Ruan et al, , 2005Shah et al, 1996;UNAIDS, 2006). Drug abuse also facilitates HIV transmission in indirect ways.…”
Section: Introductionmentioning
confidence: 98%
“…Sharing of needles and paraphernalia in particular drives the epidemic in many countries outside Africa (Aceijas, Stimson, Hickman, & Rhodes, 2004;Fuller et al, 2003;Ruan et al, 2004Ruan et al, , 2005Shah et al, 1996;UNAIDS, 2006). Drug abuse also facilitates HIV transmission in indirect ways.…”
Section: Introductionmentioning
confidence: 98%
“…Prevalence of related risk behaviors (i.e. needle sharing and unprotected sex with different types of partners) among IDU was quite high (Ruan et al, 2004a).…”
Section: Introductionmentioning
confidence: 99%
“…It ranked the 6th among all Chinese provinces in the total number of HIV cases reported [1]. Previous studies reported that the HIV prevalence among non-institutionalized IDUs ranged from 11.3 to 17.8% [3,11] and syringe sharing for drug use was also prevalent among IDUs in Sichuan [9,12]. Behavioral surveillance survey (BSS) among IDUs was conducted in Sichuan as part of the China-UK HIV/AIDS Prevention and Care Project.…”
Section: Introductionmentioning
confidence: 99%